How do perceptions of information usefulness and green trust influence intentions toward eco-friendly purchases in a social media context? - Wu, Meifen; Long, Ruyin (Frontiers in Psychology, 2024)
Drawing upon the stimulus-organism-response framework and incorporating green trust and perceptions of information usefulness, we formulated a model to explore how marketing on social media impacts consumers' intentions towards eco-friendly purchases, using eastern Chinese cities as a case study. The findings indicate that: (1) Marketing on social media significantly boosts intentions for eco-friendly purchases, and green trust positively affects the perceptions of information usefulness. (2) Green trust and perceptions of information usefulness jointly act as mediators between social media marketing and eco-friendly purchase intentions, with green trust exhibiting a stronger effect (0.306>0.122). The multi-group analysis findings indicate significant disparities in several potential pathways as a result of moderating factors such as educational attainment, etc. The benefits are especially apparent in women, people with middle to high incomes, people with intermediate to high levels of education, and people who engage with social media for over three hours per day. Through the effect analysis between marketing on social media, green trust, and perceptions of information usefulness on consumers' intentions towards eco-friendly purchases, this study offers insights to social media platforms, businesses, and policymakers, enabling them to enhance strategies for fostering eco-friendly consumer behavior through social media channels.